Virtual Reality as a Media for Learn Animal Diversity for Students - Fatma Sukmawati; Eka Budhi Santosa; Triana Rejekiningsih; Suharno; Taufiq Subhanul Qodr (Jurnal Edutech Undiksha, 2022)
In the educational process, students face various problems, one of which is the difficulty in understanding the material due to its complexity of the material. New technology-based media are being introduced that help students in the learning process, such as virtual reality (VR). This research aims to produce a product in the form of virtual reality development media as a learning medium for animal diversity. This type of research is developed using a 4D model design. The data collection method uses non-test with research instruments, namely expert validation questionnaires and user validation questionnaires. As well as data analysis techniques using descriptive analysis to describe the results of questionnaires distributed to experts, practitioners, and students as research subjects consisting of media experts, material experts, practitioners, and students. The results of the product feasibility tests carried out on media experts, material experts, and students get many positive responses. So it can be concluded that the virtual reality media of animal diversity is suitable for learning. This media makes it easy for students to understand the variety of animals and provides an attraction for students so that an increased desire to learn arises.